(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
India is a major player in the pharmaceutical industry. Currently, India is the world’s leadingsupplier of generic pharmaceuticals, accounting for 20 of worldwide exports in volume. This means thatthe Indian pharmaceutical business will outpace the worldwide pharmaceutical industry, which ispredicted to expand at a 5 annual rate between 2015 and 2020. Patent-protected generics account formore than 80 of all pharmaceutical sales (in terms of revenues). An estimated 2.4 percent of the worldpharmaceutical business in value and 10 percent in volume, the Indian pharmaceutical sector is predictedto grow at a 15.92 percent compound annual growth rate to US 55 billion by 2020 from US 20 billion in2015. This study demonstrates that the AGR of pharmaceutical imports and exports as a whole isresponsible for its growth rate.